Multi-dimensional optimization of the incorporation of PCM-drywalls in lightweight steel-framed residential buildings in different climates - Soares, N. (2014)
This paper evaluates the impact of PCM-drywalls in the annual and monthly heating and cooling energy savings of an air-conditioned lightweight steel-framed (LSF) residential single-zone building, considering real-life conditions and several European climates. A multi-dimensional optimization study is carried out by combining EnergyPlus and GenOpt tools. The CondFD-algorithm is used in EnergyPlus to simulate phase-changes. For the optimization, the PSOCC-algorithm is used considering a set of predefined discrete construction solutions. These variables are related with the thermophysical properties of the PCM (enthalpy-temperature and thermal conductivity-temperature functions), solar absortance of the inner surfaces, thickness and location of the PCM-drywalls. Several parameters are included in the model mainly those related with the air-conditioned set-points, air-infiltration rates, solar gains, internal gains from occupancy, equipment and lighting. Indices of energy savings for heating, cooling and for both heating and cooling are defined to evaluate the energy performance of the PCM-enhanced rooms. Results show that an optimum solution can be found for each climate and that PCMs can contribute for the annual heating and cooling energy savings. PCM-drywalls are particularly suitable for Mediterranean climates, with a promising energy efficiency gain of about 62% for the Csb-Coimbra climate. As for the other climates considered, values of about 10% to 46% were obtained.